Persepsi Pemustaka Atas Suara Gamelan Terhadap Tingkat Kenyamanan Literasi Di Perpustakaan Lingkungan Fakultas Seni Pertunjukan (FSP) ISI Surakarta - Sartini Sartini; Sugeng Priyanto (Institut Seni Indonesia Yogyakarta, 2021)
Riset ini dilatarbelakangi oleh fenomena efek suara gamelan yang terjadi di ruang kuliah yang terdengar hingga perpustakaan di lingkungan FSP ISI Surakarta. Yang ingin diungkap dalam riset ini adalah 1) Bagaimana pemustaka meresepsi suara gamelan ketika melakukan aktivitas literasi di Perpustakaan Lingkungan Fakultas Seni Pertunjukan? 2) Bagaimana implikasi suara gamelan terhadap tingkat kenyamanan aktivitas literasi di Perpustakaan lingkungan Fakultas Seni Pertunjukan? Untuk mengungkap permasalahan digunakan teori kenyamanan Katharine Kolcaba tentang kenyamanan psikospiritual dan kenyamanan lingkungan serta psikologi musik Djohan Salim tentang musik dan emosi manusia. Penelitian ini dilakukan mengunakan kombinasi model, atau desain sequential explanatory (urutan pembuktian), yaitu metode yang menggabungkan kuantitatif dan kualitatif secara beurutan. Tahap pertama dilakukan dengan metode kuantitatif, yakni dengan mendistribusikan kuesioner kepada para pemustaka. Lantas selanjutnya dilakukan dengan metode kualitatif meliputi: observasi, wawancara, dokumentasi, dan analisis. Hasil dari penelitian ini adalah, 1) suara gamelan dirasa tidak mengganggu. 2) Suara gamelan dianggap lazim, sebagai kampus seni, dan dirasa bukan menjadi hal yang menggangu dalam aktivitas berliterasi. 3) suara gamelan dianggap sebagian pemustaka sebagai hal yang memberikan pengaruh baik terhadap kenyamanan mereka, artinya secara psikologi memberikan dampat baik dan tentu membuat nyaman di dalam ruangan. 4) Suara gamelan dianggap tidak perlu menjadi hal yang diperdebatkan. 5) Kenyamanan selalu berbanding lurus dengan pengalaman ketubuhan manusia, suara gamelan merupakan entitas yang menjadi pengalaman mayoritas mahasiswa ISI Surakarta, sehingga di dalam aktivitas literasi tidak menjadikan gangguan secara umum. This research is motivated by the phenomenon of gamelan sound effects that occur in lecture halls which are heard to the library in the Faculty of Performing Arts at Indonesian Institute of the Arts Surakarta environment. This research wants to reveal 1) How does the user perceive gamelan sound when doing literacy activities in the Environmental Library of the Performing Arts Faculty? 2) How the implications of the voice of gamelan to the comfort level of literacy activities in the Library of the Performing Arts Faculty? To uncover the problem Katharine Kolcaba's comfort theory is used about psychospiritual comfort and environmental comfort and Djohan Salim's music psychology about music and human emotions. This research was conducted using a combination of models, or sequential explanatory designs (sequences of proof), a method that combines quantitative and qualitative sequentially. The first stage is done by quantitative methods, namely by distributing questionnaires to users. Then the next is done by qualitative methods include: observation, interviews, documentation, and analysis. The results of this research are, 1) the sound of the gamelan is consistently felt not disturbing. 2) the sound of gamelan is considered to be common, as an art campus, and is not considered to be a disturbing thing in literated activities. 3) the sound of gamelan is considered part of the visitors as a matter of good influence on their comfort, meaning psychologically giving a good impact and of course making it comfortable in the room. 4) the sound of the gamelan is unnecessarily staged. 5) comfort is always directly proportional to the experience of human body, the sound of gamelan is an entity that is the experience of the majority of Indonesia Insititute of the Arts Surakarta students, so that literacy activities do not cause general disturbance.The results of this research are, 1) the sound of the gamelan is consistently felt not disturbing. 2) the sound of gamelan is considered to be common, as an art campus, and is not considered to be a disturbing thing in literated activities. 3) the sound of gamelan is considered part of the visitors as a matter of good influence on their comfort, meaning psychologically giving a good impact and of course making it comfortable in the room. 4) the sound of the gamelan is unnecessarily staged. 5) comfort is always directly proportional to the experience of human body, the sound of gamelan is an entity that is the experience of the majority of Indonesia Insititute of the Arts Surakarta students, so that literacy activities do not cause general disturbance.